Pengembangan UMKM Melalui Pelatihan Pemasaran di Desa Perupuk Kecamatan Bandar Pusaka Kabupaten Aceh Tamiang - Muhammad Khaizir Arifin; Anjur Perkasa Alam (peduli riset dan pengabdian masyarakat, 2024)
Small and Medium Enterprises (SMEs) have a major role in national economic development. In addition to playing a role in national economic growth and employment, SMEs also play a role in the distribution of development results and are a driving force for the growth of national economic activity. Marketing is an important part of running a business. It needs good management so that the business can grow better. The MSME Training activity is one of the 2024 STAI Jam'iyah Mahmudiyah Tanjung Pura Student Community Service programmes in Perupuk Village, Bandar Pusaka District, Aceh Tamiang Regency. This programme was implemented to help build and develop MSMEs in Perupuk Village, Bandar Pusaka District. MSME players are expected to improve the quality and productivity of their businesses, so that MSME products in Perupuk Village, Bandar Pusaka Sub-district, can compete in a wider market. Through this training activity, it is hoped that MSMEs in Perupuk Village, Bandar Pusaka Sub-district will be able to improve the quality and productivity of their businesses, so that MSME products in Perupuk Village, Bandar Pusaka Sub-district can compete in a wider market. This programme consists of 4 activities, namely Product Development Class, Social Media Marketing Class, account creation and simple bookkeeping.